Three makes a family - Webb, Cari Lynn (Webb, Cari Lynn City by the bay., 2021)
Lawyer Molly McKinney needs to be the best--now more than ever. Relocating to San Francisco means a chance to provide a stable income and home for her nine-month-old daughter. And defending former rival Drew Harrington against charges of witness tampering will boost her reputation. As they work to clear Drew's name, their feelings grow. But does Molly have room in her life for love?